HASIL BELAJAR KOGNITIF FISIKA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING PADA MATERI POKOK KINEMATIKA DI KELAS XI IPA MAN I PEKANBARU - Fakhruddin Z; Nur Oktaviani (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2009)
This research was intended to describe the students cognitive achievement result through applying problemposing method in physics learning for kinemathics by vector analyzing. The subject of this reseach wasstudents of class XI IPA 1 of MAN 1 Pekanbaru which consists of 32 students. The collecting instrument ofthis research was the achievement of cognitive test in the final of the lesson. Descriptive analysis was used inthis research to analyze the students achievement, lesson effectiveness, students learning exhaustiveness andcompleteness of lesson objectives in kinemathics through vector analyzing. The result of the data analysisshowed that the students absorptiveness average is 66,3% which was categorized as enough for thisresearch, the lesson effectiveness was categorized as less effective, students classical learning exhaustivenesswas 21,9 % which categorized not complete and the lesson objectives completeness was 60% whichcategorized not complete.